The systematic analysis and 10-year prediction on disease burden of childhood cancer in China - Zhu, Bo; Wu, Xiaomei; An, Wenxiu; Yao, Bing; Liu, Yefu (Frontiers in Public Health, 2022)
Background There is a lack of in-depth analysis regarding the disease burden of childhood cancer in China. Indeed, this is the first time the topic has been addressed in detail. Drawing on population-based data for the past 30 years, this study systematically analyzes the composition and long-term trend of this disease burden in China. Methods GBD 2019 contained population-based data from 1990 to 2019 and was prepared using Microsoft Excel 2016. We used AAPC and ARIMA models for trend analysis and prediction formulation. Results In 2019, there were 45,601 new cases, 9,156 cancer deaths, and 782,530 DALYs in China. From 1990 to 2019, leukemia, together with brain and CNS cancer, invariably ranked highest in terms of new cases, cancer deaths, and DALYs. Leukemia accounted for more than 50%, but decreased over time. By contrast, the proportions for brain and CNS cancer increased. There were significant decreases in the overall incidence, mortality, and DALY rates in China, but these were still higher than the corresponding global average levels. Considering all types of childhood cancer, the incidence rate of testicular cancer showed the biggest increase, and the mortality and DALY rates of leukemia showed the largest decrease. In terms of different age groups, the overall incidence rate of childhood cancers increased in 0 to 4 age group, but it decreased in 5 to 14 age groups. The overall mortality and DALY rates of childhood cancers decreased in all four age groups. Over the next 10 years, the overall incidence rate of childhood cancer will increase, but the overall mortality and DALY rates will decrease. The increase in malignant skin melanoma will comprise the largest rise in the incidence, while the decrease for leukemia will be the largest fall in the incidence, cancer deaths, and DALYs. Conclusion The disease burden of all childhood cancers in China remains highly serious, especially for certain types of cancer and certain age groups. China should focus more emphatically on the incidence of childhood cancer in future, and it must consistently strengthen investment in the relevant research and medical resources to reduce the disease burden in this field.